Hegemonic constraints : the implications of September 11 for American power - Goh, Evelyn (2009)
This paper argues that at the heart of the post - September 11 world lies several critical issues surrounding American power : its unprecedented primacy, the way in which it is exercised and how it is perceived and received around the world. On the one hand, September 11 not only failed to alter American preponderance of power in the international system, but in fact reinforced US credibility, power projection and militery involvement abroad. On the other hand, this 'new' terrorism and the American response have undermined critical elements of US 'soft' power in the international arena, even as its 'hard' power has been reinforced. Notwithstanding its unipolar status, the terrorist assaults on the American homeland demonstrated dramatically that the US faces significant unorthodox challenges beyond the realm of great power competition. September 11 and the US responses to it have impacted significantly upon the vital 'soft' foundations of American power: the appeal of American values and culture; the perception that US hegemony is benign; and the apparent legitimacy of the exercise of American power. The terrorist attacks triggered off a questioning of American character and behaviour by their dramatic challenge to US values and ideology. At the same time, this process has served to highlight the negative and sometimes malign effects of American projections of power. Furthermore, Washington's reactions to the attacks have fuelled controversy and have sensitised the international community to questions regarding the legitimacy of American actions and policies. These trends, if they continue, will, in the longer term, serve to constrain the exercise of American power by limiting the choice and effectiveness foreign and security policies. These constraints will operate at two levels: at the international level, Washington will experience increased friction and costs in dealing with its allies and other friendly states; and at the domestic level, the Bush and subsequent administrations will have to take into accound rising public unwillingness to pay the more extreme price of external interventions.